1981
DOI: 10.1038/bjc.1981.250
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of preoperative serum CEA level compared to clinical staging. I. Colorectal carcinoma

Abstract: Summary.-In a clinical investigation of observed postoperative survival, 563 patients have been registered for primary surgical treatment of colorectal cancer since 1974. The potential prognostic factors examined within the first days of hospitalization for primary resection included age of the patients, operability, location of the tumour, tumour extension and the preoperative serum CEA level. Statistical treatment of the data revealed that each of the clinical parameters except tumour location covers ranges … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
2
3

Year Published

1982
1982
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 12 publications
(8 reference statements)
0
16
2
3
Order By: Relevance
“…When these patients were included, some differences in survival of patients with distinct tumour extension became less or no more significant (Table I). The prognostic significance of the age classes < 70 and > 70 years, recently reported by us in colorectal-cancer patients (Staab et al, 1981) was not found in the present group of stomach-cancer patients.…”
Section: Discussioncontrasting
confidence: 39%
See 1 more Smart Citation
“…When these patients were included, some differences in survival of patients with distinct tumour extension became less or no more significant (Table I). The prognostic significance of the age classes < 70 and > 70 years, recently reported by us in colorectal-cancer patients (Staab et al, 1981) was not found in the present group of stomach-cancer patients.…”
Section: Discussioncontrasting
confidence: 39%
“…A positive correlation with survival was reported for patients with lung cancer (Concannon et al, 1978;Vincent et al, 1979;Stokes et al, 1980;Ford et al, 1981) and colorectal cancer (Kohler et al, 1980;Staab et al, 1981), a positive correlation with disease recurrence was reported for patients with resected colorectal cancer (Wanebo et al, 1978;Evans et al, 1978;Goslin et al, 1980) and cervix cancer (Kjorstad & 0rjasaeter, 1982). The prognostic significance of the preoperative CEA level was still evident when selected subgroups of patients with distinct resectability and tumour extension were examined (Staab et al, 1981) thus representing a prognostic marker independent of resectability and clinical staging. These findings open up the possibility of including preoperative measurements of serum CEA concentration in the set of prognostic parameters, such as resectability and tumour extension, which can be established within a few days, during hospitalization of patients for primary treatment.…”
mentioning
confidence: 99%
“…Goslin et al [12] and Lewi et al [24] showed Journal of Surgical Oncology that higher preoperative CEA levels are associated with poorer prognosis only in Dukes' C disease, and not Dukes' B disease. In contrast, after reviewing 563 colorectal cancer patients, Staab et al [25] reached a different conclusion. They reported that the differences between survival curves based on preoperative CEA ranges of <5 and >5 ng/ml are significant for patients with TNM stage II tumors (P < 0.02) but not for patients with lymph node metastases (P ¼ 0.1).…”
Section: Discussionmentioning
confidence: 95%
“…The results of several major series involving many hundred patients have been published during the past few years. Some of the investigators are convinced by the sub-sets that can be created within the Dukes (1938) or TNM classifications of colorectal cancer (UICC, 1978) by adding an arbitrary discriminant level of CEA, for example > 5 ng ml -1 carry important prognostic information (Staab et al, 1981;Wanebo et al, 1978;Szymendra et al;; for others the prognostic significance of a low CEA level is dubious. (Goslin et al, 1980;Blake et al, 1982).…”
Section: Discussionmentioning
confidence: 99%
“…There is now a large body of evidence that preoperative high blood levels of carcinoembryonic antigen (CEA) in colorectal cancer and in gastric cancer will be associated with a decreased survival, especially of patients with locally advanced or metastatic tumours (Staab et al, 1981(Staab et al, , 1982Wanebo et al, 1978). However, the prognostic significance of slightly raised levels of CEA is still debatable (Goslin et al, 1980;Blake et al, 1982;Steel et al, 1982).…”
mentioning
confidence: 99%